Addressing sustainability: A strategy development framework - Galbreath, Jeremy (Inderscience, 2009)
Some pundits have gone as far as to suggest that sustainability represents a shift equal in magnitude to the industrial revolution. While perhaps an audacious claim, sustainability nonetheless is capturing the attention of business firms, governments and consumers. Consumers, for example, place the highest burden on business to address sustainability. Surprisingly, however, many executives appear to be unclear as to what their long-term strategy should be, given sustainability. The purpose of this paper is to add to the strategy-sustainability discussion and explain a conceptual framework that addresses the focal topic. The framework is not restricted to a single dimension of sustainability, such as the natural environment, or to a single sector, like the manufacturing sector. Second, the framework contains five key dimensions and focuses explicitly on strategy making, grounded in sound theory. Lastly, to address practicality, a case study of the company, Whole Foods Market, is presented to elaborate on the framework.